2017
DOI: 10.1108/jocm-07-2016-0139
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between subjective well-being and workplace ostracism

Abstract: Purpose The purpose of this paper is to examine the effect of subjective well-being (SWB) on workplace ostracism, by focusing on the moderating role of emotional intelligence (EI). SWB is taken here as a construct of three components: life satisfaction, positive affect (PA), and negative affect (NA). Design/methodology/approach The theoretical model was tested using data collected from employees in different firms from different provinces in China. Analyses of multisource and lagged data from 677 employees i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…However, positive affectivity refers to an individual's tendency to experience enthusiasm and positive emotions over time and across situations (Watson et al, 1987). Scholars have argued that individuals high in NA are more likely to perceive higher levels of ostracism than individuals high in PA (Mao et al, 2017;Zhang & Shi, 2017). According to the person-situation interaction theory (Mischel, 1968(Mischel, , 1977, an individual's attitudinal and behavioral response to a situation is a by-product of their perceptions of the situation and their personality characteristics.…”
Section: Predictors Of Workplace Ostracism: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, positive affectivity refers to an individual's tendency to experience enthusiasm and positive emotions over time and across situations (Watson et al, 1987). Scholars have argued that individuals high in NA are more likely to perceive higher levels of ostracism than individuals high in PA (Mao et al, 2017;Zhang & Shi, 2017). According to the person-situation interaction theory (Mischel, 1968(Mischel, , 1977, an individual's attitudinal and behavioral response to a situation is a by-product of their perceptions of the situation and their personality characteristics.…”
Section: Predictors Of Workplace Ostracism: Hypothesesmentioning
confidence: 99%
“…First, I provide a meta‐analytic review of the predictors and consequences of victims’ perceptions of workplace ostracism (referred to as workplace ostracism from this point forward). Several scholars have suggested that individual personality traits and skill sets may predispose them to perceive higher or lower levels of ostracism (Leung, Wu, Chen, & Young, 2011; Mao Liu, Jiang, & Zhang, 2017; Yaakobi & Williams, 2016b; Zhang & Shi, 2017). Empirical studies on the influence of these individual characteristics, however, have provided inconclusive results.…”
Section: Introductionmentioning
confidence: 99%
“…As a uniquely painful experience ( Robinson et al, 2013 ), ostracism has negative effects on employees’ behaviors and attitudes. Some studies have shown that ostracism is negatively related to psychological well-being ( Xu et al, 2015 ; Zhang and Shi, 2017 ) and belongingness ( O’Reilly and Robinson, 2009 ; O’Reilly et al, 2015 ), but positively related to emotional exhaustion ( Wu et al, 2012 ), job tension ( Zhu et al, 2017 ), and depression ( Ferris et al, 2008 ; Scott and Duffy, 2015 ). Ostracized employees may enter a state of distress, anxiety, depression, and possibly even meaninglessness ( Wu et al, 2012 ; O’Reilly et al, 2015 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Emotional Intelligence has now been well-defined with a certain set of carefully chosen words that convey a deep meaning and understanding and read out as "using social intelligence with the ability to manage and understand one's own emotions and the emotions of others to ultimately add to the intelligent quotient of self and use the gathered information later for discriminating between right and wrong". Employees that have a high level of emotional intelligence have proven themselves to be better at dealing with the implications that arise from them being subjected to workplace ostracism (Zhang & Shi, 2017). Its common for individuals to go through a variety of feelings when they face ostracism, these emotions includes anger, anguish, pain, depression, anxiety or irritation etc.…”
Section: Emotional Intelligencementioning
confidence: 99%